Analisis Tindak Tutur pada Tayangan Channel Youtube Metro TV, Kiky Saputri dan Ate Roasting Pasangan Calon Presiden 01 Tahun 2024 (Kajian Pragmatik) - Asmirawanti, Asmirawanti; Safar, Muh.; Asdar, Muhammad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to analyze the forms of speech in YouTube Metro TV shows in the Kiky Saputri and Ate segment while roasting the pair of presidential candidates for the Republic of Indonesia 01 in 2024. This study uses a pragmatic approach with a focus on three types of speech acts, namely locution, illocution, and perlocution. The research method used is qualitative descriptive with data collection techniques through documentation studies from videos lasting 34 minutes and 16 seconds. The results of the study showed that in the show there were various forms of locution speech in the form of statements, questions, and the delivery of literal information. The acts of illocution speech found included commands, sarcasm, and praise which were categorized into assertive, directive, expressive, and commissive functions. Meanwhile, the act of perlocution speech is seen through the reaction of the audience and speech partners which shows the success of communication in the context of humor and social criticism. These findings show that speech in the context of roasting not only contains elements of entertainment, but also conveys certain intentions and has an effect on listeners. This research is expected to contribute to the development of pragmatic studies, especially in understanding the function and strategy of language in social media, as well as becoming a reference for language educators and practitioners in fostering polite language awareness in the digital public space.